We've updated our
Privacy Policy effective December 15. Please read our updated Privacy Policy and tap

Study Guides > College Algebra

Equations With Radicals and Rational Exponents

Learning Objectives

  • Solve a radical equation, identify extraneous solution
  • Solve an equation with ratinal exponents
Radical equations are equations that contain variables in the radicand (the expression under a radical symbol), such as
3x+18=xx+3=x3x+5x3=2\begin{array}{l}\sqrt{3x+18}\hfill&=x\hfill \\ \sqrt{x+3}\hfill&=x - 3\hfill \\ \sqrt{x+5}-\sqrt{x - 3}\hfill&=2\hfill \end{array}
Radical equations may have one or more radical terms, and are solved by eliminating each radical, one at a time. We have to be careful when solving radical equations, as it is not unusual to find extraneous solutions, roots that are not, in fact, solutions to the equation. These solutions are not due to a mistake in the solving method, but result from the process of raising both sides of an equation to a power. However, checking each answer in the original equation will confirm the true solutions.

A General Note: Radical Equations

An equation containing terms with a variable in the radicand is called a radical equation.

How To: Given a radical equation, solve it.

  1. Isolate the radical expression on one side of the equal sign. Put all remaining terms on the other side.
  2. If the radical is a square root, then square both sides of the equation. If it is a cube root, then raise both sides of the equation to the third power. In other words, for an nth root radical, raise both sides to the nth power. Doing so eliminates the radical symbol.
  3. Solve the remaining equation.
  4. If a radical term still remains, repeat steps 1–2.
  5. Confirm solutions by substituting them into the original equation.

Example: Solving an Equation with One Radical

Solve 152x=x\sqrt{15 - 2x}=x.

Answer: The radical is already isolated on the left side of the equal side, so proceed to square both sides.

152x=x(152x)2=(x)2152x=x2\begin{array}{l}\sqrt{15 - 2x}\hfill&=x\hfill \\ {\left(\sqrt{15 - 2x}\right)}^{2}\hfill&={\left(x\right)}^{2}\hfill \\ 15 - 2x\hfill&={x}^{2}\hfill \end{array}
We see that the remaining equation is a quadratic. Set it equal to zero and solve.
0=x2+2x15=(x+5)(x3)x=5x=3\begin{array}{l}0\hfill&={x}^{2}+2x - 15\hfill \\ \hfill&=\left(x+5\right)\left(x - 3\right)\hfill \\ x\hfill&=-5\hfill \\ x\hfill&=3\hfill \end{array}
The proposed solutions are x=5x=-5 and x=3x=3. Let us check each solution back in the original equation. First, check x=5x=-5.
152x=x152(5)=525=555\begin{array}{l}\sqrt{15 - 2x}\hfill&=x\hfill \\ \sqrt{15 - 2\left(-5\right)}\hfill&=-5\hfill \\ \sqrt{25}\hfill&=-5\hfill \\ 5\hfill&\ne -5\hfill \end{array}
This is an extraneous solution. While no mistake was made solving the equation, we found a solution that does not satisfy the original equation. Check x=3x=3.
152x=x152(3)=39=33=3\begin{array}{l}\sqrt{15 - 2x}\hfill&=x\hfill \\ \sqrt{15 - 2\left(3\right)}\hfill&=3\hfill \\ \sqrt{9}\hfill&=3\hfill \\ 3\hfill&=3\hfill \end{array}
The solution is x=3x=3.

Try It

Solve the radical equation: x+3=3x1\sqrt{x+3}=3x - 1

Answer: x=1x=1; extraneous solution x=29x=-\frac{2}{9}

Solve Equations With Rational Exponents

Rational exponents are exponents that are fractions, where the numerator is a power and the denominator is a root. For example, 1612{16}^{\frac{1}{2}} is another way of writing 16\sqrt{16}; 813{8}^{\frac{1}{3}} is another way of writing  83\text{ }\sqrt[3]{8}. The ability to work with rational exponents is a useful skill, as it is highly applicable in calculus. We can solve equations in which a variable is raised to a rational exponent by raising both sides of the equation to the reciprocal of the exponent. The reason we raise the equation to the reciprocal of the exponent is because we want to eliminate the exponent on the variable term, and a number multiplied by its reciprocal equals 1. For example, 23(32)=1\frac{2}{3}\left(\frac{3}{2}\right)=1, 3(13)=13\left(\frac{1}{3}\right)=1, and so on.

A General Note: Rational Exponents

A rational exponent indicates a power in the numerator and a root in the denominator. There are multiple ways of writing an expression, a variable, or a number with a rational exponent:
amn=(a1n)m=(am)1n=amn=(an)m{a}^{\frac{m}{n}}={\left({a}^{\frac{1}{n}}\right)}^{m}={\left({a}^{m}\right)}^{\frac{1}{n}}=\sqrt[n]{{a}^{m}}={\left(\sqrt[n]{a}\right)}^{m}

Example: Evaluating a Number Raised to a Rational Exponent

Evaluate 823{8}^{\frac{2}{3}}.

Answer: Whether we take the root first or the power first depends on the number. It is easy to find the cube root of 8, so rewrite 823{8}^{\frac{2}{3}} as (813)2{\left({8}^{\frac{1}{3}}\right)}^{2}.

(813)2=(2)2=4\begin{array}{l}{\left({8}^{\frac{1}{3}}\right)}^{2}\hfill&={\left(2\right)}^{2}\hfill \\ \hfill&=4\hfill \end{array}

Try It

Evaluate 6413{64}^{-\frac{1}{3}}.

Answer: 14\frac{1}{4}

Example: Solving an Equation Involving Rational Exponents and Factoring

Solve 3x34=x123{x}^{\frac{3}{4}}={x}^{\frac{1}{2}}.

Answer: This equation involves rational exponents as well as factoring rational exponents. Let us take this one step at a time. First, put the variable terms on one side of the equal sign and set the equation equal to zero.

3x34(x12)=x12(x12)3x34x12=0\begin{array}{l}3{x}^{\frac{3}{4}}-\left({x}^{\frac{1}{2}}\right)\hfill&={x}^{\frac{1}{2}}-\left({x}^{\frac{1}{2}}\right)\hfill \\ 3{x}^{\frac{3}{4}}-{x}^{\frac{1}{2}}\hfill&=0\hfill \end{array}
Now, it looks like we should factor the left side, but what do we factor out? We can always factor the term with the lowest exponent. Rewrite x12{x}^{\frac{1}{2}} as x24{x}^{\frac{2}{4}}. Then, factor out x24{x}^{\frac{2}{4}} from both terms on the left.
3x34x24=0x24(3x141)=0\begin{array}{l}3{x}^{\frac{3}{4}}-{x}^{\frac{2}{4}}\hfill&=0\hfill \\ {x}^{\frac{2}{4}}\left(3{x}^{\frac{1}{4}}-1\right)\hfill&=0\hfill \end{array}
Where did x14{x}^{\frac{1}{4}} come from? Remember, when we multiply two numbers with the same base, we add the exponents. Therefore, if we multiply x24{x}^{\frac{2}{4}} back in using the distributive property, we get the expression we had before the factoring, which is what should happen. We need an exponent such that when added to 24\frac{2}{4} equals 34\frac{3}{4}. Thus, the exponent on x in the parentheses is 14\frac{1}{4}. Let us continue. Now we have two factors and can use the zero factor theorem.
x24(3x141)=0x24=0x=03x141=03x14=1x14=13Divide both sides by 3.(x14)4=(13)4Raise both sides to the reciprocal of 14.x=181\begin{array}{ll}{x}^{\frac{2}{4}}\left(3{x}^{\frac{1}{4}}-1\right)\hfill&=0\hfill & \hfill \\ {x}^{\frac{2}{4}}\hfill&=0\hfill & \hfill \\ x=0\hfill & \hfill \\ 3{x}^{\frac{1}{4}}-1\hfill&=0\hfill & \hfill \\ 3{x}^{\frac{1}{4}}\hfill&=1\hfill & \hfill \\ {x}^{\frac{1}{4}}\hfill&=\frac{1}{3}\hfill & \text{Divide both sides by 3}.\hfill \\ {\left({x}^{\frac{1}{4}}\right)}^{4}\hfill&={\left(\frac{1}{3}\right)}^{4}\hfill & \text{Raise both sides to the reciprocal of }\frac{1}{4}.\hfill \\ x\hfill&=\frac{1}{81}\hfill & \hfill \end{array}
The two solutions are x=0x=0, x=181x=\frac{1}{81}.

Try It

Solve: (x+5)32=8{\left(x+5\right)}^{\frac{3}{2}}=8.

Answer: {1}\{-1\}

Licenses & Attributions